2017
DOI: 10.1002/aoc.4203
|View full text |Cite
|
Sign up to set email alerts
|

Denitrogenative Pd/Cu‐catalyzed Suzuki‐type Cross‐coupling of Aryltrifluoroborates with Arylhydrazine Hydrochlorides in Water under Room Temperature

Abstract: A water‐soluble palladium‐catalyzed Suzuki‐type cross‐coupling of aryltrifluoroborates with arylhydrazide hydrochlorides was efficiently developed under mild and environmentally benign conditions, in water without any ligand. The newly developed Pd/Cu co‐catalyzed denitrogenative reaction gave a range of structurally diverse substituted biaryls with good to excellent yields, in which the byproduct was nitrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…4‐Methoxy‐1,1′‐biphenyl (3a): Purification by flash chromatography (SiO 2 , hexane/ethyl acetate, 98:2) afforded the product as a white solid: by using iodobenzene ( 1c ) as acceptor and 4‐methoxyphenylzinc iodide ( 2a ) as donor 549 mg (2.98 mmol, 90 %) were obtained, by using 4‐iodoanisole ( 1a ) as acceptor and phenylzinc iodide ( 2c ) as donor 543 mg (2.95 mmol 89 %) were obtained. The NMR spectroscopic data agree with the literature . 1 H NMR (401 MHz, CDCl 3 ): δ = 7.57 (t, J = 8.5 Hz, 4 H), 7.44 (t, J = 7.6 Hz, 2 H), 7.32 (t, J = 7.3 Hz, 1 H), 7.00 (d, J = 8.7 Hz, 2 H), 3.87 (s, 3 H) ppm.…”
Section: Methodssupporting
confidence: 87%
“…4‐Methoxy‐1,1′‐biphenyl (3a): Purification by flash chromatography (SiO 2 , hexane/ethyl acetate, 98:2) afforded the product as a white solid: by using iodobenzene ( 1c ) as acceptor and 4‐methoxyphenylzinc iodide ( 2a ) as donor 549 mg (2.98 mmol, 90 %) were obtained, by using 4‐iodoanisole ( 1a ) as acceptor and phenylzinc iodide ( 2c ) as donor 543 mg (2.95 mmol 89 %) were obtained. The NMR spectroscopic data agree with the literature . 1 H NMR (401 MHz, CDCl 3 ): δ = 7.57 (t, J = 8.5 Hz, 4 H), 7.44 (t, J = 7.6 Hz, 2 H), 7.32 (t, J = 7.3 Hz, 1 H), 7.00 (d, J = 8.7 Hz, 2 H), 3.87 (s, 3 H) ppm.…”
Section: Methodssupporting
confidence: 87%
“…Qi and co-workers reported that palladium/copper can be used to co-catalyze denitrogenative cross-coupling reactions of arylhydrazines and potassium aryltrifluoroborates at room temperature (Scheme 7). [19] A wide variety of biaryls could be produced in high yields utilizing this approach, which used 2 mol % CuCl 2 •H 2 O as the co-catalyst and water as the solvent.…”
Section: Reactions With Organoboron Reagentsmentioning
confidence: 99%
“…Very recently, Wang and co-workers reported an extension of Pd-catalyzed Suzuki coupling of arylhydrazines to the potassium aryltrifluoroborate coupling partners. 16 Thus, in the presence of only 1 mol% of water-soluble Pd(NH 3 ) 2 Cl 2 as a catalyst, 2 mol% of CuCl 2 ·2H 2 O as a co-catalyst and 1.0 equiv. of K 2 CO 3 as a base in water at room temperature, C–C coupling of (het)aryltrifluoroborates 7 with (het)arylhydrazide hydrochlorides 8 furnished functionalized biaryls 9 in good to excellent yields ( Scheme 4 ).…”
Section: Carbon–carbon Cross-couplingsmentioning
confidence: 99%